Direct matric suction measurement of unsaturated soils - Ho, Lun Fa (2015)
In general, residual soils are unsaturated and have negative pore-water pressure. Hence, measuring the pore-water pressure of such soils is not as straightforward as measuring pore-water pressure of saturated soils. The direct measurement of unsaturated soils by a conventional tensiometer is constrained to pore-water pressure of more than -100 kPa due to cavitation which inhibit the ability of tensiometer to read any higher negative pore-water pressure. The objective of this project was to determine the matric suction of unsaturated residual soil directly and to investigate cavitation which led to the inability of tensiometer to record high negative pore-water pressure. A soil-water characteristic curve plotted from pressure plate test and chilled-mirror dew-point technique helped to correlate the water content of soil specimens to its relevant matric suction, which would be useful for comparison of matric suction determined from the tensiometer. An acrylic tensiometer block, which incorporated a pressure transducer, hydrophone and a 15 bar ceramic disk into a single system, included a water reservoir that is much larger than the typical 10 mm3 water reservoir of high capacity tensiometers. The tensiometer block was saturated by applying a constant pressure of 2500 kPa for a month. Free evaporation test was conducted to establish the matric suction measurement capacity of the tensiometer block. The acrylic tensiometer block was used to conduct the matric suction measurement of consolidated residual soils. A soundproof box was constructed with plywood and acoustic foam to reduce the amplitude of ambient noise which may prevent the accurate detection of cavitation sound produced from the water reservoir in the tensiometer block via the hydrophone. For the trials relating to local cavitation within the soil specimen without a pressure transducer, no significant variations in wave amplitude was detected by the hydrophone. Therefore, no conclusive evidence of cavitation occurrence, if any, could be obtained based on the hydrophone measurement. The initial free evaporation test carried out on the tensiometer block after two weeks of pressurisation showed slow pore-water response from the slow drop in pressure. However, the free evaporation test after a month of pressurisation illustrated slightly faster response. But only a maximum sustainable suction of 103.9 kPa could be obtained after 3967 seconds. This was attributed to the large volume of water present in the water reservoir of the tensiometer block which had a greater number of potential nuclei and hence implied a higher possibility of cavitation occurring at low suction.